The little nugget - Wodehouse, P. G. (Pelham Grenville), 1881-1975 (Harmondsworth, Middlesex : Penguin Books, 1959)
The son of an American millionaire, Ogden Ford--Little Nugget--arrives at Sanstead House School and the crazy fun begins. The director is a snob, the schoolmaster a gem, and Little Nugget is a handful!
Keywords: Humorous stories